Here's the question you clicked on:

55 members online
  • 0 replying
  • 0 viewing

0214

  • 3 years ago

If f(x) = −2x − 1 and g(x) = 6x − 1, find f[g(−2)]

  • This Question is Closed
  1. bahrom7893
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 2

    g(-2) = -12-1=-13 f(-13) = -2*-13-1=26-1=25

  2. precal
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    |dw:1352648848925:dw|

  3. precal
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    |dw:1352648880837:dw|

  4. precal
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    another way to do it,but the above method given is also, correct

  5. Not the answer you are looking for?
    Search for more explanations.

    • Attachments:

Ask your own question

Sign Up
Find more explanations on OpenStudy
Privacy Policy